2007
DOI: 10.1213/01.ane.0000267257.45752.31
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leaving Dentures in Place on Bag-Mask Ventilation at Induction of General Anesthesia

Abstract: We conclude that bag-mask ventilation is easier in edentulate patients when their dentures are left in situ during induction of general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…If this was not achieved, it was then mandatory to use ancillary techniques to ensure adequate bag-mask ventilation. These techniques were defined as a secondary outcome and included the increasing of FGF to 6 L/min, closure of the APL valve to 30 cm H 2 O, and use of the oxygen flush device and two-person technique (the resident using two hands to secure the mask while an assistant squeezing the bag) [9]. …”
Section: Methodsmentioning
confidence: 99%
“…If this was not achieved, it was then mandatory to use ancillary techniques to ensure adequate bag-mask ventilation. These techniques were defined as a secondary outcome and included the increasing of FGF to 6 L/min, closure of the APL valve to 30 cm H 2 O, and use of the oxygen flush device and two-person technique (the resident using two hands to secure the mask while an assistant squeezing the bag) [9]. …”
Section: Methodsmentioning
confidence: 99%
“…The results showed no link between lack of teeth and mask ventilation; however, other studies have shown that mask ventilation is more difficult in edentulous patients. Several previous studies have described the difficulties experienced by elderly patients during mask ventilation (4,7,14,16,17). However, very few studies have investigated the insertion of laryngeal masks and the possible problems related to this process in patients in this age group (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…This loss of structure creates a gap between the cheeks and the mask. 18,19 Using 2 hands to pull the patient's cheeks to oppose the mask during mask ventilation often helps minimize leak. Recreating structure can be achieved by leaving the dentures in place 18 or by packing the patient's cheeks with gauze, 20 although the latter risks foreign object obstruction or aspiration.…”
Section: Inadequate Seal At the Mask-patient Interfacementioning
confidence: 99%